Merger Bank Umum Sebagai Implikasi Peraturan Bank Indonesia No.8/16/PBI/2006 Tentang Kebijakan Kepemilikan Tunggal Perbankan Indonesia - , Rendra Hakim ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Issuance of Bank Indonesia No.8/16/PBI/2006 About Ownership Sole Banking Indonesia has been applied in the banking world of Indonesia, especially for those who have become the controlling shareholder in more than one bank, they are given three choices for an option to adjust the structure ownership of one of the three options is to choose the merger option, on one hand with the merger could reduce the number of banks in Indonesia so that it will facilitate supervision by Bank Indonesia, on the other hand the merger of a bank shall be guided by the laws and regulations in Indonesia, and mergers also give effect to the minority shareholders in which the law should protect them from a merger. This study aims to determine how the legal procedures of a bank merger, what are the benefits and disadvantages of the merger, and how the legal protection of minority shareholders of the merged banks choose an option. This research is legal, normative empirically by using source data obtained from literature, as for the analysis of qualitative research conducted to analyze the data obtained in a systematic, factual and accurate, and discuss the doctrines or principles in the science of law to draw a conclusion to answer the problem under study. The results of the discussion are: (1) the procedure for doing mergers of commercial banks regulated in PP. 27 of 1998 and Decree No. BI Directors. 32/51/KEP/DIR and also guided by the Company Law, which the merger procedure consists of five stages of the preparation phase, implementation phase, the stage of application for a license, permit entry into force of the merger phase, and the reporting phase of the implementation of the merger, (2) the benefits of mergers may increase the capital a bank and can also reduce the number of existing banks so as to facilitate the Bank Indonesia in conducting surveillance, (3) the merger has an impact on minority shareholders, which should be given legal protection of minority shareholders by providing appraisal rights which the company must buy back their stock at a reasonable price.